A modified k - &epsilon; model of turbulence - Chowdhury, Showkat Jahan (Journal of Mechanical Engineering, 2008)
In this paper, the parameters of a thermodynamically consistent k - ε model of turbulence are first determined, and the numerical values of the various model coefficients are evaluated. Limiting flows of a decaying homogeneous turbulence, turbulent flow in the inertial sublayer, and known properties of purely diffusive turbulence are used for this purpose. The thermodynamically consistent model is then incorporated into an enhanced version of the TEACH computer code called STARPIC. Finally, the modified computational code is used to simulate the flow through a channel to assess its capability in predicting turbulent flows. The computational results are compared with available experimental data, and found to have reasonable matching. The flows are also simulated using standard k - ε model, for comparison. It is observed that the present thermodynamically consistent modified k - ε model predictions are better compared to the standard k - ε model predictions. DOI: 10.3329/jme.v38i0.895 Journal of Mechanical Engineering Vol.38 Dec. 2007 pp.14-17